AB0324 Dose reduction of tocilizumab in rheumatoid arthritis patients with low disease activity: a pilot study. (23rd January 2014) - van Herwaarden, N.; Herfkens-Hol, S.; van der Maas, A.; van den Bemt, B.; van Vollenhoven, R.; Bijlsma, J.; den Broeder, A.
Abstract : Background: Tocilizumab, in the registered dose of 8 mg/kg, has proven to be an effective treatment in rheumatoid arthritis (RA) patients. However, RCT data show that a substantial proportion of patients can achieve low disease activity on a lower than registered (4 versus 8mg/kg) starting dose 1 . A lower dose might reduce dose-dependent side effects and costs. No data, however, are available on the feasibility of dose reduction to 4 mg/kg in RA patients who reached low disease activity on the registered dose of 8 mg/kg. Objectives: To examine the proportion of RA patients with successful dose reduction of tocilizumab after achieving low disease activity, and to asses the frequency of secondary ineffectiveness after re-escalation. Methods: According to the local treatment protocol, RA patients start with tocilizumab 8mg/kg every 4 weeks. After at least 6 months of successful treatment, the dose is reduced to 4 mg/kg if patients have low disease activity(DAS28<3.2 and judgement of rheumatologist). In case of loss of disease control (DAS28>3.2 and judgement of rheumatologist) the dose is increased again to 8mg/kg. In this observational pilot study, patient, disease and treatment characteristics were collected as well as data on disease activity before and after dose reduction and when applicable after dose re-escalation. Results: In 19 patients tocilizumab dose was reduced because of low disease activity. The mean disease duration in those patients was 11 years (SD 8.4), rheumatoid factor positive 68%, anti-CCP positive 81% and erosive disease 58%. The mean DAS28 at time of dose reduction was 2.4 (SD 0.9). After 3 and 6 months follow up, respectively 73% (CI 49-90%) and 53% (CI 31-79%) of the patients still had low disease activity on the dose of 4mg/kg. The DAS28 at respectively 3 and 6 months was somewhat (ns) higher than baseline, 2.9 (SD 1.3) and 2.8 (SD 1.0). Most RA flares (78%) after dose reduction occurred in the first 16 weeks. All patients who experienced worsening of disease activity after dose reduction regained low disease activity after dose re-escalation. Conclusions: Dose reduction of tocilizumab is feasible in a substantial proportion of patients. Dose re-escalation after flare was effective in all patients. References: Kremer JM et al, Arthritis&Rheumatism 2011;63(3):609-21 Disclosure of Interest: N. van Herwaarden: None Declared, S. Herfkens-Hol: None Declared, A. van der Maas: None Declared, B. van den Bemt: None Declared, R. van Vollenhoven Grant/research support from: Abbott, BMS, GSK, MSD, Pfizer, Roche, UCB, Consultant for: Abbott, BMS, GSK, MSD, Pfizer, Roche, UCB, J. Bijlsma Consultant for: Abbott, Roche, BMS, UCB, Pfizer and Merck, A. den Broeder: None Declared